Three Years Survival of Elderly Cancer Patients in Indonesia: Do We Need a Different Approach? - Noorwati Sutandyo; Sri Agustini Kurniawati; Nia Novianti Siregar; Nina Kemala Sari (Interna Publishing, 2020)
Background: the number of elderly people in Indonesia is increasing. Additionally, cancer prevalence among older patients is also increasing. However, studies assessing clinical factors associated with the survival of elderly patients with cancer are still lacking. This study aimed to investigate the survival of geriatric patients with cancer and associated factors. Methods: this was a retrospective cohort study. Subjects were geriatric patients with cancer aged >60 years, enrolled between 2013 and 2015 in Dharmais Cancer Hospital. Data were retrieved from medical records and consisted of gender, age, cancer type, stage, Eastern Cooperative Oncology Group (ECOG) performance status (PS), body mass index (BMI), Charlson Comorbidity Index, and type of treatment. Cox regression analysis was used to identify independent prognostic factors for survival. Results: a total of 249 patients were enrolled, with a median age of 66 (60-85) years. The most common cancer was of the lung, followed by breast, colorectal, and uterine cervical cancers. The median survival time was 24 months. Cox multivariate analysis was performed by gender stratification. Advanced stage cancer (III-IV) was identified as the risk factor for mortality in female patients (hazard ratio [HR] 2.72; 95% confidence interval [CI] 1.53-4.80; p = 0.001), while poor performance status (ECOG 2 - 4) was the risk factor in male group (HR 1.82; 95% CI 1.01-3.24; p = 0.04). Conclusion: the survival of elderly patients with cancer is affected by traditional prognostic factors. Advanced cancer stage was significant independent prognostic factor in female patients, while poor performance status was significant in male patients.